PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS DI SD N 35 PALEMBANG - Mutiara Rosalina; Muhammad Juliansyah Putra; Farhan yadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether the Picture And Picture learning model has an effect on students' interest in learning IPAS at SD N 35 Palembang. This study is a quantitative research using the Quasy Experiment method. Data collection techniques include questionnaires and documentation. The study was conducted on class 5A, consisting of 25 students as the experimental group, and class 5C, consisting of 28 students as the control group. The instrument used was a questionnaire comprising 20 statements. The results of this study indicate that there is an effect of the Picture and Picture learning model on students' interest in learning the IPAS subject at SD N 35 Palembang, with a calculated t-value (4.165) > table t-value (1.676) and a significance level (0.000) < (0.05). Consistent with the hypothesis testing, if the calculated t-value is greater than the table t-value, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted